Responsible management in Asia : perspectives on CSR - Williams, Geoffrey (Basingstoke : Palgrave MacMillan, 2011)
'... covers the history and development of corporate social responsibility (CSR) in Asia and how it has helped to create pathways to social and environmental sustainability across the region.'--Back cover.
Includes bibliographical references and index.
Keywords: Social responsibility of business -- Asia